Dual Vocational Students Competency: A Second Order Confirmatory Factor Analysis of Occupational Competency in Enterprise - Somchat Boonsri; Phadungchai Pupat; Peerawut Suwanjan (My University, 2019)
Abstract Due to rapid change in technology, enterprises are facing a shortage of competent human resources that are suitable for their needs. The Dual Vocational Training Program, which emphasizes authentic training for enterprises, is able to develop human resources from vocational education so that their competencies are up to date competencies, to keep up with technological changes. The purpose of this study was to conduct a second order confirmatory factor analysis of occupational competencies in enterprises. The samples of this study were 804 students of the Vocational Education Certificate Program, in the field of Mechanical Technology. They were selected by using Multi-Stage Random Sampling. The instrument used was a 5 level rating scale questionnaire. The results of the study indicated that the Model of Occupational Competency in Enterprise of Dual Vocational Training Students is valid. The structural equation statistical values were: Chi-square = 896.0707, df = 514, p = .000, χ2/df = 1.47 (less than 2.0), GFI = .945, AGFI = .920, and RMSEA = .030.
Keywords: Economic shortage; Certificate; Competency Development and Evaluation